1998
DOI: 10.1002/jlb.63.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of human neutrophil oxidative burst by polychlorinated biphenyls: inhibition of superoxide dismutase activity

Abstract: We report evidence of a novel mechanism by which polychlorinated biphenyls might act as potent inducers of inflammation. Aroclor 1242 (A1242), a polychlorinated biphenyl mixture, and 2,2',4,4'-tetrachlorobiphenyl (PCB47), a constituent of A1242 that produces the same patterns of effects, impaired the oxidative burst of human neutrophils by inhibiting the antioxidant enzyme superoxide dismutase, which converts O 2 ؊ to H 2 O 2 . Pre-incubation of neutrophils with A1242 or PCB47 before stimulation with phorbol 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Neutrophils were distinguished from monocytes as described previously. 9 Northern Blot Analysis of ICAM-1 and Monocyte Chemoattractant Protein-1 Standard Northern blotting was used to investigate monocyte chemoattractant protein-1 (MCP-1) and ICAM-1 mRNA expression, and ribosomal protein L32 (rpL32) was used as a housekeeping gene for normalization. Primers were designed according to published sequences.…”
Section: Flow Cytometric Analysis Of Surface Expression Of Cd11b Cd1mentioning
confidence: 99%
“…Neutrophils were distinguished from monocytes as described previously. 9 Northern Blot Analysis of ICAM-1 and Monocyte Chemoattractant Protein-1 Standard Northern blotting was used to investigate monocyte chemoattractant protein-1 (MCP-1) and ICAM-1 mRNA expression, and ribosomal protein L32 (rpL32) was used as a housekeeping gene for normalization. Primers were designed according to published sequences.…”
Section: Flow Cytometric Analysis Of Surface Expression Of Cd11b Cd1mentioning
confidence: 99%
“…TCDD and few other dioxin like compounds induce formation of toxic proteins which might have created the intracellular toxic load. TCDD, PCBs and other PAH chemicals are reported to be interacting with AhR which can initiate the formation of apoptosome or trigger apoptosis [17] . Though it is not very clear at this moment but the results of the present study indicated the observed nephrotoxicity by TCDD was probably caused by some byproduct or intermediate compounds produced elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…After 30 min. of incubation, superoxide anion and hydrogen peroxide productions were equal from PMA stimulated neutrophils (Narayanan et al 1998). Therefore, oxidative burst measured as hydrogen peroxide production is reliable.…”
Section: Oxidative Burst Assaymentioning
confidence: 99%
“…The conversion of DHR to its fluorescent derivative, Rh-123, was assessed 30 min. after PMA stimulation and incubation at 37°C in CO 2 atmosphere (Narayanan et al 1998). After 30 min.…”
Section: Oxidative Burst Assaymentioning
confidence: 99%